Manajemen Pendidikan Secara Manusiawi: Studi Kasus Terhadap Manajemen Pengajaran Tenaga Pendidik Man 2 Brebes Di Bumiayu - Asikin, Asikin (International Conference of Moslem Society, 2016)
The number of productive age of Indonesian population will reach the highest rate in the year 2035. Thisachievement actually begins in 2010. Since it is something new after this nation got its freedom, the government makes a lot of effort to make sure that the large number of productive age population is in line with its high quality as well. The linearity of quantity and quality is then called by the demographic bonus (bonus demografi) which the national development enables to take advantage of it. However, if the condition both the quantity and the quality of the population is upside down between one to another itpossibly becomes disastrous demographic (bencana demografi) (Kemendikbud, 2013: 7). Many efforts have been carried out to pursue the demographic bonus. One of them is through the national education together with its management which emphasizes on pupils’ integrated multi-intelligence. Education and management are like two sides of coin. It brings many issues. One of them is about humane education management issue. Most of educators and experts pay a little attention tothe humane education management in the teaching and learning activities (KBM, for short) in this country since they think it naturally goes on. At State Islamic Senior high School (MAN,for short) 2 Brebes is one for instance. Becoming the only state Islamic State Senior High School in southern District of Brebes, MAN 2 Brebes experiences quite good progress in the last five (5) years due to the academic and non-academic achievement. This paper describes the humane education management implemented by educators in MAN 2 Brebes. The type of research used in this paper is a qualitative case study approach. The research location is at MAN 2 Brebes. The subjects of the study consisted of Principal, Vice-Principals, Teachers, students and also Administration Staff. The Data Collection technique in this research is taken through interview, observation, documentation, and questionnaire. The data validation test is done by triangulation and data collection techniques. The data analysis was performed with data reduction, display and conclusion. The result showed that humane education management that is carried out humanly in MAN 2 Brebes treats the learners humanely rather than the reverse such as bullying done by teachers or among students, theft, and other crime. Humane education management conducted in MAN 2 Brebes has a number of purposes. Among others are: 1). giving motivation for students, 2). initiating to self-concept, 3). Developing and improving creativity, 4). leading to positive curiosity, 5). reducing anxiety, and 6). escaping from being a stranger at madrasa.